Geriatric health policy in India: The need for scaling-up implementation - N Sherin Susan Paul; Mathew Asirvatham (Journal of Family Medicine and Primary Care, 2016)
In an anticipation of the rising geriatric population in India, the Central government constituted the National Policy for Older Persons in 1999 to promote the health and welfare of senior citizens in India. A major strategy of this policy is to encourage families to take care of their older family members. The policy also encourages voluntary organizations to supplement the care provided by the family and provide care and protection to vulnerable elderly people. The implementation of this policy, particularly in the rural areas, has been negligible and calls for a scaling-up of programs to address the physical, psychological, and social needs of the poor. Due to breakdown of the joint family system and the migration of the younger generation to the towns and cities, the elderly parents in the villages are left to fend for themselves. Too old to work and with little or no source of income, the elders are struggling even to satisfy their basic needs. This article primarily focuses on the various facets of elderly care in India. As a fledgling nation in elderly care, we should take cues from other nations who have pioneered in this field and should constantly evolve to identify and face the various challenges that come up, especially from rural India. The Rural Unit for Health and Social Affairs Department of a well-known Medical College in South India has developed a “senior recreation day care” model which proves to be a useful replicable model to improve the quality of life and nutritional status of the elderly in the lower rungs of society. More than a decade since its inception, it is now the right time to assess the implementation of our geriatric health policy and scale-up programs so that the elderly in our country, irrespective of urban and rural, will have a dignified and good quality life.